A bone matrix‐simulating scaffold to alleviate replicative senescence of mesenchymal stem cells during long‐term expansion. Issue 9 (2nd May 2020) - Su, Xiaoxia; Jing, Huan; Yu, Wenting; Lei, Fengzhen; Wang, Rui; Hu, Cheng; Li, Mujia; Lin, Tingting; Zhou, Hong; Wang, Fei; Liao, Li
Abstract: Replicative senescence during in vitro augmentation, which is mostly induced by the loss of physiological microenvironment, hinders the application of mesenchymal stem cells (MSCs) in the clinic. Here, we investigated whether MSCs senescence could be prevented by bio‐scaffold mimicking the natural tissue matrix. Human umbilical cord mesenchymal stem cells (hUCMSCs) exhibited a senescent phenotype during a long‐term passage in the conventional culture dish. To fabricate the bone matrix, a naturally based matrix composed of nano‐hydroxyapatite/chitosan/poly lactide‐co‐glycolide (nHA/CS/PLGA) was produced. Long‐term passage resulted in an obvious increase in the expression of senescence markers and a reduction in the expression of master genes involved in tissue regeneration. Functional assay confirmed that nHA/CS/PLGA scaffold preserved the proliferation and differentiation of hUCMSCs even after being passaged 27 times. Moreover, in vivo ectopic bone formation assay revealed that the bone formation of hUCMSCs cultured on the nano‐scaffolds for the long term was as robust as the cells in the early passage. In summary, our results demonstrate that nHA/CS/PLGA scaffold effectively preserves the stemness and youth of hUCMSCs in the long‐term passage. Taken advantage of its compatibility and bioactivity, nHA/CS/PLGA scaffold is of great potential in large‐scale expansion of MSCs for stem cell therapy and tissue engineering.